1998
DOI: 10.1002/aic.690440602
|View full text |Cite
|
Sign up to set email alerts
|

Trailing vortices around a 45° pitched‐blade impeller

Abstract: The trailing vortex system near impeller blades has been identified as the major flow mechanism responsible for mixing and dispersion in stirred vessels

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
65
3
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 22 publications
12
65
3
3
Order By: Relevance
“…Similar investigations on such transition may be found in the works of Hockey (1990) and Hockey & Nouri (1996). Schäfer et al (1998) observed by means of flow visualisation the flow discharged by a 45° PBT to be directed axially at higher Re and radially at lower Re. The flow stream direction was unstable, varying from radial to axial, for Re = 490-510.…”
Section: Classification Of Flow Instabilitiessupporting
confidence: 56%
“…Similar investigations on such transition may be found in the works of Hockey (1990) and Hockey & Nouri (1996). Schäfer et al (1998) observed by means of flow visualisation the flow discharged by a 45° PBT to be directed axially at higher Re and radially at lower Re. The flow stream direction was unstable, varying from radial to axial, for Re = 490-510.…”
Section: Classification Of Flow Instabilitiessupporting
confidence: 56%
“…In the entire vertical plane, midway between two baf es, velocities have been measured in a nely spaced grid by Schäfer et al 9 , see Figure 3(a). The average upward ow close to the tank wall only extends over a limited axial distance.…”
Section: Resultsmentioning
confidence: 99%
“…In the experimental work 9 , the Reynolds number (de ned as Re ND 2 =n, with N the angular velocity of the impeller (in rev s 1 ), D the diameter of the impeller, and n the kinematic viscosity of the uid) was set to 7,300. A cubic computational domain, consisting of 120 3 , 240 3 , or 360 3 grid nodes was de ned.…”
Section: Set-up Of the Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Für die Vermessung turbulenter Rührwerksströmungen eignet sich insbesondere die Laser-Doppler-Anemometrie, da sie zum einen in stark instationären und hochturbulenten Strömungsgebieten verlässliche Informationen liefert und zum anderen berührungslos arbeitet, so dass die Strömung nicht beeinflusst wird [28], [87], [88]. Bei dieser Methode wird durch zwei sich kreuzende, kohärente Laserstrahlen ein Interferenzmuster, bestehend aus hell-dunkel-Streifen, erzeugt.…”
Section: Beschreibung Des Lda-messverfahrensunclassified